Is Mobile Money Part of Money? : Understanding the Trends and Measurement - Shirono, Kazuko (IMF Working Papers; Working Paper, 2021)
The rapid uptake of mobile money in recent years has generated new data needs and growing interest in understanding its impact on broad money. This paper reviews mobile money trends using mobile money data from the Financial Access Survey (FAS) and examines the statistical treatment of mobile money under the IMF's Monetary and Financial Statistics (MFS) framework. MFS guidance is straightforward in most cases, as many jurisdictions have adopted regulations which ensure that mobile money is captured in the banking system and thus in the calculation of broad money. However, in cases where mobile network operators (MNOs) act as niche financial intermediaries outside the banking regulatory perimeter and are allowed to invest their customer funds in sovereign securities and other permitted assets, mobile money liabilities may remain outside the banking system as well as monetary statistics. In that case, information on mobile money liabilities need to be collected directly from MNOs to account for mobile money as part of broad money.